Micronutrient adequacy and morbidity: Paucity of information in children with cerebral palsy - Schoendorfer, N.; Boyd, Roslyn; Davies, P. (2010)
A literature review was conducted to investigate the status of vitamins and minerals in children with cerebral palsy and the implications of various deficiencies on health outcomes. Children with cerebral palsy commonly have feeding difficulties, which significantly impact their growth, general health, and life expectancy. Current nutritional literature focuses on energy expenditure, with little information available on other parameters, such as micronutrient status. Due to the paucity of micronutrient research in these children, the impacts of deficiencies and benefits in other populations have been considered. The role of micronutrients in maintaining cellular homeostasis throughout all body systems highlights a need for future research and monitoring of their levels, particularly in vulnerable populations with well-documented incidence of undernutrition. © 2010 International Life Sciences Institute.